Media Pembelajaran Interaktif “Batik Pedia” Berbasis Aplikasi Android Pada Ensiklopedia Batik Nusantara - Alief Fathul Habibie; Fachira Nur Sahfitri; Welia Desera Mandalika (LKP KARYA PRIMA KURSUS, 2023)
Batik is a traditional textile art form originating from Java, Indonesia. This involves using wax to design patterns on cloth, which are then dyed to create the effect of many colors. The batik process involves several steps including waxing, dipping and boiling the cloth to remove the wax. Batik has a long history in Indonesia and is an important part of the country's cultural heritage. It is often used to make decorative fabrics such as clothing and tablecloths. Batik has grown in popularity around the world in recent years, with many designers incorporating this technique into their collections. Batik is a comprehensive resource on the history and techniques of Batik, Indonesia's traditional textile art. This encyclopedia provides structured information about the origins and cultural significance of batik, and how batik has developed over time. Some of the topics discussed in this Batik Encyclopedia include the history of batik, batik patterns and designs, the manufacturing process, and the tools used to make batik, as well as fun and certainly interesting quizzes. In this study, the authors used a qualitative descriptive approach and an IMSDD development method which would later be implemented into an Android-based application using Microsoft PowerPoint, Ispring Suite, and the APK 2 website builder. With the interactive application